Analysis of the expression of putative heat-stress related genes in relation to thermotolerance of cork oak - Correia, Barbara; Rodriguez, José Luis; Valledor, Luis; Almeida, Tânia; Santos, Conceição; Cañal, Maria Jesus; Pinto, Glória (Journal of Plant Physiology, 2014)
Cork oak (Quercus suber L.) is a research priority in the Mediterranean area and because of cork oaks’ dis- tribution these stands are experiencing daily stress. Based on projections of intensifying climate change and considering the key role of exploring the recovery abilities, cork oak seedlings were subjected to a cumulative temperature increase from 25◦C to 55◦C and subsequent recovery. CO2 assimilation rate, chlorophyll fluorescence, anthocyanins, proline and lipid peroxidation were used to evaluate plant per- formance, while the relative abundance of seven genes encoding for proteins of cork oak with a putative role in thermal/stress regulation (POX1, POX2, HSP10.4, HSP17a.22, CHS, MTL and RBC) was analyzed by qPCR (quantitative Polymerase Chain Reaction). A temperature change to 35◦C showed abundance alterations in the tested genes; at 45◦C, the molecular changes were associated with an antioxidant response, possibly modulated by anthocyanins. At 55◦C, HSP17a.22, MTL and proline accumulation were evident. After recovery, physiological balance was restored, whereas POX1, HSP10.4 and MTL abundances were suggested to be involved in increased thermotolerance. The data presented here are expected to pinpoint some pathways changes occurring during such stress and further recovery in this particular Mediterranean species. ©
Keywords: high temperature; Plant performance; Quercus suber; Recovery

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M M; Pereira, J S; MAROCO, J; RODRIGUES, M L; RICARDO, C P P; OSÓRIO, M L; CARVALHO, I; Faria, T; PINHEIRO, C (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M. M.; Pereira, J. S.; MAROCO, J.; Rodrigues, M. L.; RICARDO, C. P. P.; OSÓRIO, M. L.; CARVALHO, I.; FARIA, T.; PINHEIRO, C. (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf10510.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle